Design and implementation of a smart agrivoltaic system - Mahjabin, Maliha; Hasan, Almas Samin; Ahmed, Tanvir; Abdullah, Fahad Bin (Brac University, 2024)
This final year design project is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2023.